The determination of international jurisdiction in international sales and purchases. Consumer or non-consumer? That is the key - Noriega Linares, Carmen María (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
International jurisdiction in matters of international sales and purchases is an issue that can be of great interest, but can also present difficulties. It is important to determine the role of each of the parties involved in the contractual relationship, because depending on who is involved, different criteria will be applied to attribute jurisdiction to the courts of one State or another. Furthermore, contracting over the Internet may lead one to think that the matter is complex, but nothing could be further from the truth. Technologies are advancing, but, in many cases, the legal cases that arise are well known and the rules to be applied are the usual ones.
Keywords: internet sales and purchases; burden of proof; consumer; Brussels I-bis Regulation; plea of nullity